2021
DOI: 10.1016/j.ijom.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Oral management with polaprezinc solution reduces adverse events in haematopoietic stem cell transplantation patients

Abstract: Oral management with polaprezinc solution reduces adverse events in haematopoietic stem cell transplantation patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…[ 28 ] Moreover, oral management significantly decreased the incidence of oral adverse events (oral mucositis) during treatment, before and after HSCT in inpatients with hematopoietic neoplasms. [ 29 , 30 ] Systemic antibiotic prophylaxis, such as the preoperative administration of metronidazole and amoxicillin combination, is reportedly effective in improving the treatment outcomes and prognosis of patients with severe periodontitis [ 31 , 32 ] and HSCT. [ 33 ] Despite strong evidence of the role of oral health in the prevention of life-threatening infections in hematology inpatients, to our knowledge, an association between oral health assessments and the detection of GNB in hematology inpatients has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 28 ] Moreover, oral management significantly decreased the incidence of oral adverse events (oral mucositis) during treatment, before and after HSCT in inpatients with hematopoietic neoplasms. [ 29 , 30 ] Systemic antibiotic prophylaxis, such as the preoperative administration of metronidazole and amoxicillin combination, is reportedly effective in improving the treatment outcomes and prognosis of patients with severe periodontitis [ 31 , 32 ] and HSCT. [ 33 ] Despite strong evidence of the role of oral health in the prevention of life-threatening infections in hematology inpatients, to our knowledge, an association between oral health assessments and the detection of GNB in hematology inpatients has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Yamada et al indicated that myelosuppressed/immunosuppressed conditions in cancer treatment require intervention during the perioperative oral management [28] . Moreover, oral management significantly decreased the incidence of oral adverse events (oral mucositis) during treatment, before and after HSCT in inpatients with hematopoietic neoplasms [29,30] . Systemic antibiotic prophylaxis, such as the preoperative administration of metronidazole and amoxicillin combination, is reportedly effective in improving the treatment outcomes and prognosis of patients with severe periodontitis [31,32] and HSCT [33] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, all controls needed opioids against the 30% of children who received P-AG [20]. Eventually, Tsubura-Okubo et al observed the reduction in pain, taste disorders, and incidence of oral mucositis by rinsing and swallowing ZnC in polyacrylic acid solution (PPAA) in patients that received chemotherapy and HSCT [22]. In addition, the severity of acute graft-versus-host disease (GVHD) was significantly lower in patients that received PPAA than in controls [22].…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, Tsubura-Okubo et al observed the reduction in pain, taste disorders, and incidence of oral mucositis by rinsing and swallowing ZnC in polyacrylic acid solution (PPAA) in patients that received chemotherapy and HSCT [22]. In addition, the severity of acute graft-versus-host disease (GVHD) was significantly lower in patients that received PPAA than in controls [22]. Taste disorders are another intraoral clinical application of ZnC because zinc is a cofactor of taste buds' enzymes [6].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Yamagata et al reported that dental treatment to control infected areas and sources of infection with proper cleaning procedures prior to HSCT treatment resulted in the absence of any dental infections in the patients after transplantation [21]. Moreover, oral management signi cantly decreased the incidence of oral adverse events (oral mucositis) during treatment before and after HSCT in inpatients with hematopoietic neoplasms [22,23].…”
Section: Introductionmentioning
confidence: 99%